1991
DOI: 10.2307/3869210
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Mutants in Arabidopsis: The Consequences of Duplicated Tryptophan Synthase b Genes

Abstract: The cruciferous plant Arabidopsis thaliana has two closely related, nonallelic tryptophan synthase beta genes (TSB1 and TSB2), each containing four introns and a chloroplast leader sequence. Both genes are transcribed, although TSB1 produces greater than 90% of tryptophan synthase beta mRNA in leaf tissue. A tryptophan-requiring mutant, trp2-1, has been identified that has about 10% of the wild-type tryptophan synthase beta activity. The trp2-1 mutation is complemented by the TSB1 transgene and is linked genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…There are several examples of duplication of tryptophan pathway genes (39)(40)(41)(42) with substantial evidence that one acts in tryptophan production while the other affords intermediates for production of defensive secondary metabolites (43)(44)(45). In Ruta graveolens, one of the duplicate genes for anthranilate synthase alpha (AS␣2) is constitutive and the corresponding enzyme is feedback-inhibited by L-tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…There are several examples of duplication of tryptophan pathway genes (39)(40)(41)(42) with substantial evidence that one acts in tryptophan production while the other affords intermediates for production of defensive secondary metabolites (43)(44)(45). In Ruta graveolens, one of the duplicate genes for anthranilate synthase alpha (AS␣2) is constitutive and the corresponding enzyme is feedback-inhibited by L-tryptophan.…”
Section: Discussionmentioning
confidence: 99%
“…The His biosynthesis mutant hpa1 resembles tup5-1 insofar as it has a short root when grown in vitro, but there is no obvious phenotype in the aerial part and hpa1 mutants are fully fertile plants (Mo et al, 2006). Mutants for several Trp biosynthetic pathway genes are generally impaired in development under high-light but not under low-light conditions (Last et al, 1991;Radwanski et al, 1996). It has been suggested that the residual activity of the mutant enzyme might be able to cover the lower Trp demand of slowgrowing plants in low light (Last et al, 1991).…”
Section: Tup5-1 Mutants Show An Unusual Blue Light-dependent Root Gromentioning
confidence: 99%
“…Mutants for several Trp biosynthetic pathway genes are generally impaired in development under high-light but not under low-light conditions (Last et al, 1991;Radwanski et al, 1996). It has been suggested that the residual activity of the mutant enzyme might be able to cover the lower Trp demand of slowgrowing plants in low light (Last et al, 1991). In contrast, the roots and shoots of soil-grown tup5-1 plants grown under standard light develop normally, though high metabolic activity can be expected under these conditions.…”
Section: Tup5-1 Mutants Show An Unusual Blue Light-dependent Root Gromentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the higher expression levels of CYP74B2 (HPL) transcripts and volatiles produced, these data suggest that the levels of JAs are also elevated in Ler leaves compared to Col leaves. Also interesting among the set more highly expressed in the Ler ecotype are several loci in aliphatic glucosinolate synthesis, including CYP79F1, which exists upstream of CYP83A1 (Hansen et al, 2001;Reintanz et al, 2001;Chen et al, 2003), CYP83A1 itself, and 2-oxoglutarate-dependent dioxygenase (AOP3), which exists downstream of CYP83A1 (Kliebenstein et al, 2001b); Trp synthetase (TSB2; Last et al, 1991) also potentially impacts aliphatic glucosinolate synthesis because it is postulated to feed substrates into the aliphatic glucosinolate pathway via CYP79B2 and CYP79B3 . Contrasting with these glucosinolate synthetic enzymes that are more highly expressed in the Ler ecotype, one locus more highly expressed in the Col ecotype codes for thioglycosyl hydrolase (TGG2, myrosinase), which degrades glucosinolates to release toxic derivatives (Xue et al, 1995).…”
Section: Transcript Profiling In Col and Ler Ecotypesmentioning
confidence: 99%